Lectina relacionada ao fibrinogênio do ouriço-do-mar Echinometra lucunter: isolamento, sequência de aminoácidos e atividade antimicrobiana - Duarte, Philippe Lima (2021)
One of the first lines of defense for invertebrates is related to the recognition of pathogens by standard recognition receptors/proteins (PRRs/PRPs) and recognition molecules. Among them, fibrinogen-related proteins (FRePs) that are identified in invertebrates stand out, and that, in their majority, act as PRPs playing important roles in microbial agglutination, bacterial lysis and clearance and in antiparasitic defense. A fibrinogen-related lectin called ELL was isolated from the coelomic fluid of the sea urchin Echinometra lucunter by affinity chromatography on xanthan gum. ELL is a dimer composed of 25 kDa subunits, joined by a disulfide bond. The new lectin was inhibited by glycoproteins such as porcine stomach mucins type II and III (PSM II, PSM III), bovine submaxillary mucin (BSM) and thyroglobulin. The amino acid sequence of ELL was determined by mass spectrometry. The ELL monomer consists of 229 amino acids, including seven cysteines involved in three conserved intrachain disulfide bonds and an interchain disulfide bond. The complete ELL sequence has conserved motifs and fibrinogen domain in the typical C-terminal portion of fibrinogen-related proteins. A threedimensional model of ELL was predicted by homology, revealing that the protein has two carbohydrate recognition domains (CRDs), CRD A is located in the N-terminal region and appears to interact with N-acetyl-mannosamine and CRD B is found in the C-terminal and can bind to N-acetyl-galactosamine. In assays of antimicrobial activity, ELL was able to inhibit the growth of pathogenic Gram-positive bacteria, in addition to reducing the biomass and cell viability of the biofilm formed by Gram-positive and Gram-negative bacteria, showing its ability to recognize pathogens, in addition to antimicrobian activity.